Stable isotope analysis of Dublin Bay food web - Laurand, Sandrine (Trinity College (Dublin, Ireland). Department of Zoology, 2017)
Coastal ecosystems are being increasingly impacted by human activities. Among the main threats, eutrophication is a major issue worldwide which can lead to major dysfunctions such as the excessive development of opportunistic macroalgae that affect benthic communities. Impacts of such macroalgal blooms on the food webs are however poorly understood. Dublin Bay has had a long history of organic pollution and eutrophication through urban sewage which induces, among other symptoms, severe green macroalgal blooms. The bay yet sustains valuable habitats and high ecological functions but its trophic functioning remains relatively unknown. This work characterises the benthic food web of Dublin Bay, identifying the basal sources supporting it and the major pathways of carbon transfer, and explores the impacts of macroalgal blooms and the influence of a changing regime of sewage particulates inputs on the food web functioning. For this, a carbon and nitrogen stable isotope analysis was applied seasonally (4 surveys), in combination with hydrobiological measurements of the particulate organic matter (POM), through an extensive field study of five sites featuring contrasted oceanic influence and exposition to the watershed ...
Keywords: Zoology, Ph.D.; PhD Trinity College Dublin, 2017